Seasonal and diurnal variations of particulate nitrate and organic matter at the IfT research station Melpitz - L. Poulain (Atmospheric Chemistry and Physics, 2011)
Ammonium nitrate and several organic compounds such as dicarboxylic acids (e.g. succinic acid, glutaric acid), some Polycyclic Aromatic Hydrocarbon (PAHs) or some n-alkanes are semi-volatile. The transition of these compounds between the gas and particulate phase may significantly change the aerosol particles radiative properties, the heterogeneous chemical properties, and, naturally, the total particulate mass concentration. To better assess these time-dependent effects, three intensive field experiments were conducted in 2008–2009 at the Central European EMEP research station Melpitz (Germany) using an Aerodyne Aerosol Mass Spectrometer (AMS). Data from all seasons highlight organic matter as being the most important particulate fraction of PM1 in summer (59%) while in winter, the nitrate fraction was more prevalent (34.4%). The diurnal variation of nitrate always showed the lowest concentration during the day while its concentration increased during the night. This night increase of nitrate concentration was higher in winter (ΔNO3− = 3.6 μg m−3) than in summer (ΔNO3− = 0.7 μg m−3). The variation in particulate nitrate was inherently linked to the gas-to-particle-phase equilibrium of ammonium nitrate and the dynamics of the atmosphere during day. The results of this study suggest that during summer nights, the condensation of HNO3 and NH3 on pre-existing particles represents the most prevalent source of nitrate, whereas during winter, nighttime chemistry is the predominant source of nitrate. During the summer 2008's campaign, a clear diurnal evolution in the oxidation state of the organic matter became evident (Organic Mass to Organic Carbon ratio (OM/OC) ranging from 1.65 during night to 1.80 during day and carbon oxidation state (OSc) from −0.66 to −0.4), which could be correlated to hydroxyl radical (OH) and ozone concentrations, indicating a photochemical transformation process. In summer, the organic particulate matter seemed to be heavily influenced by regional secondary formation and transformation processes, facilitated by photochemical production processes as well as a diurnal cycling of the substances between the gas and particulate phase. In winter, these processes were obviously less pronounced (OM/OC ranging from 1.60 to 1.67 and OSc from −0.8 to −0.7), so that organic matter apparently originated mainly from aged particles and long range transport.